Care Transitions to and from the National Intrepid Center of Excellence (NICoE) for Service Members with Traumatic Brain Injury - Ayer, Lynsay (RAND Corporation, 2015)
The U.S. Department of Defense established the National Intrepid Center of Excellence (NICoE) to provide specialized services for troops suffering from traumatic brain injury (TBI). Through interviews with NICoE staff, home station providers, service members treated at the NICoE, and their families, as well as surveys and site visits, RAND evaluated interactions between the NICoE and providers referring patients and implementing treatment plans.